Statistical analysis of the influence of defects on fatigue life using a Gumbel distribution. (July 2018) - Anderson, K.V.; Daniewicz, S.R.
Highlights: Location and scale parameters impact the mean and standard deviation of fatigue life. A modified strip-yield model reasonably approximates S-N curves. Initial crack sizes following a Gumbel distribution yield log-normal fatigue lives. Abstract: Location and scale parameters, λ and δ, of a Gumbel distribution are used to quantify defects in metallic materials. To determine the impact of these parameters on fatigue life performance and variability, fatigue crack growth simulations of 7075-T651 aluminum alloy were performed using a modified strip-yield model to produce S-N data. It was observed that defects representing initial crack lengths following a Gumbel distribution yield a fatigue life that follows a log-normal distribution. It was determined that location and scale parameters impact the fatigue life mean and standard deviation, but have little to no effect on the coefficient of variation.